Asymmetric permittivity enhanced bilayer polycaprolactone nanofiber with superior inner interfacial polarization and charge retention for high-output and humidity-resistant triboelectric nanogenerators. (July 2022) - Zhong, Jixin; Hou, Xiaojuan; He, Jian; Xue, Feng; Yang, Yun; Chen, Liang; Yu, Junbin; Mu, Jiliang; Geng, Wenping; Chou, Xiujian
Abstract: High-output triboelectric nanogenerators (TENGs) are promising complements of chemical batteries in wearable systems. However, the charge dissipation on tribomaterials in moisture environments remains a challenge impacting the stable energy supply. Herein, asymmetric permittivity manipulation is proposed as a novel strategy to simultaneously improve the output performances and humidity resistance of TENGs. An electrospinning bilayer polycaprolactone (PCL) nanofiber (BPF) composed of outer PCL and inner PCL/CNTs nanofibers which differ widely in permittivity is served as the efficient positive tribomaterial. Benefitting from the increased friction area and dual interfacial polarization in the bilayer dielectric, the transferred charge of the BPF-TENG increases by 740% compared to the PCL gel film-based device, reaching 210 nC at 1 Hz. Significantly, a high-speed camera system verifies that the porous hydrophobic PCL nanofiber with a water contact angle of 125 degrees can effectively reduce the accumulation of water droplet on the material surface, contributing to stable output from 20% to 80% relative humidity. The optimized BPF-TENG generates a high peak-to-peak voltage of 2.24 kV and a power density of 54 W/m 2 in 80% humidity. Besides, by harvesting biomechanical energy, a 1000 µF capacitor can be charged to 3 V and continuously drive electronics to work in wet weather. This strategy can be extended to various commercialized tribo-negative polymers and enables large-scale industrial manufacturing of high-output and humidity-resistant TENGs. Graphical Abstract: A high-output and humidity-resistant triboelectric nanogenerator (TENG) based on asymmetric permittivity enhanced bilayer polycaprolactone nanofiber is proposed. Owing to the porous hydrophobic surface and interfacial polarization enhancement in bilayer dielectric, the TENG generates a high peak-to-peak output voltage of 2240 V and instantaneous power density of 54 W/m 2, as well as high voltage retention of 73% in 90% humidity, showing excellent potential in wearable power sources. ga1 Highlights: A highly tribopositive, hydrophobic, and asymmetric permittivity enhanced bilayer PCL nanofiber (BPF) is fabricated. The enhanced specific surface area and interfacial polarization promote a 740% improvement of transferred charge. A high-speed camera verifies that the PCL fiber can effectively reduce the accumulation of water droplet in high humidity. The BPF-TENG generates a high peak-to-peak voltage and power density of 2.24 kV and 54 W/m 2 by palm flapping in 80% RH.